Intramuscular hemorrhage during rehabilitation in a post-stroke patient with vascular Ehlers-Danlos syndrome: a case report and review of spasticity-related muscle injury - Izumi, Rina; Hayashi, Koji; Sato, Mamiko; Yamaguchi, Tomohisa; Suzuki, Asuka; Nakaya, Yuka; Ikeda, Kazumi; Ikawa, Masamichi; Kobayashi, Yasutaka (Frontiers in Rehabilitation Sciences, 2025)
We present the first documented case of vascular Ehlers-Danlos syndrome (vEDS) associated with muscle injury in a spastic muscle following a stroke, which occurred during physical therapy. The patient was a 46-year-old male with a family history of subarachnoid hemorrhage (SAH) and aortic dissection, who presented with sudden headache, dysarthria, and left hemiparesis, leading to transport to a nearby hospital. He was diagnosed with arterial dissection and subsequent SAH and cerebral infarction in the right hemisphere using brain computed tomography (CT) and magnetic resonance imaging (MRI). He received treatment with antihypertensive and antiplatelet medications. After five weeks, he was admitted for rehabilitation with moderate left-sided hemiparesis and spasticity. Twenty-six weeks post-onset, while participating in passive hamstring stretching, he experienced sudden pain and swelling in his left thigh. Imaging confirmed hematomas in the biceps femoris and semitendinosus muscles, indicating muscle injury. Clopidogrel was discontinued due to progressive anemia, and the hematoma resolved within five days. He quickly resumed ambulation with increasing independence. One month after the injury, he was discharged home, and subsequent genetic testing at another institution confirmed the diagnosis of vEDS with a pathogenic variant in COL3A1. Patients with vEDS are at an increased risk for injuries due to tissue fragility. A stroke can lead to limb spasticity, making spastic muscles more susceptible to injury during sudden stretching, such as passive stretching. This report highlights the need for clinicians to exercise caution when rehabilitating vEDS patients, especially in the absence of established guidelines. Further case reports and clinical evidence are essential to develop comprehensive rehabilitation standards for vEDS.